ANALISIS KUALITATIF TERHADAP PEMBUKTIAN DAN PENALARAN MATEMATIS SISWA SMA DITINJAU DARI TINGKAT ADVERSITY QUOTIENT - Arudin, - (2022)
This study aims to determine the level of adversity quotient in students, the ability to prove and reason mathematically and determine associations with the ability to prove and reason mathematically the level of adversity quotient of quitter , camper and climber types in the material of mathematical induction, arithmetic sequences and series. This research is a descriptive study using a qualitative approach. The subjects of this study were obtained by carrying out an adversity quotient test using the adversity response profile questionnaire instrument developed by Stoltz (2000) which was attended by 70 students of class XI in a high school in Bandung. The results of the adversity response profile questionnaire and filling out the test questions of students' mathematical proof and reasoning abilities classified from 70 students to 12 students. Of the 12 students, 3 students were taken from the quitter type, 5 students from the camper type and 4 students from the climber type. Of the 3 quitter type students, 1 student was selected at the low level of proof and reasoning ability and 2 students at the moderate level of proof and reasoning ability. From 5 Camper type students, who were selected were 1 student at a low level of proof and reasoning ability, 2 students at a moderate level of proof and mathematical reasoning ability and 2 students at a high level of proof and reasoning ability. While from 4 climber type students, 2 students at moderate level of proof and reasoning ability and 2 students at high level of proof and reasoning ability were selected. The results of the student's mathematical proof and reasoning ability test showed that for the quitter type , low and moderate level of proof and reasoning skills could only solve mathematical proof problems in the basic steps while the reasoning ability indicator only proposed conjectures and determined mathematical manipulations. The camper type is not much different from the quitter type in medium and low level proof and reasoning skills, but for high level proof and reasoning abilities students in the camper type can solve problems of proof and mathematical reasoning abilities well, although there are some mistakes and errors in the process. Meanwhile, for the climber type, students with moderate level of proof and reasoning ability in solving it, there are errors and errors in the induction step for proofing abilities, while for reasoning abilities the errors in the calculation process are indicators of mathematical manipulation. In high level proving and reasoning abilities, climber type students can solve problems very well. There is an association between students' mathematical proving and reasoning abilities on the adversity quotient of the two schools. Keywords : adversity quotient , ability to prove and reason, association